The Effect of Information Services Through Documentary Film Media on Social Media Addiction in Students - Sekartresna, Awang Normalanda; Yudha Wastuti, Sri Ngayomi (INDONESIAN COUNSELING AND PSYCHOLOGY, 2024)
This study aims to determine the effect of information services through documentary films on social media addiction in Angkasa Lanud Soewondo Junior High School students, the sample in this study were 27 students in class VII A. This type of research is quantitative research with experimental methods, namely one group pretest-posttest degin, data collection techniques in this study are using observation, documentation and questionnaires totaling 27 items. Based on the results of the Paired Sample Test hypothesis using SPSS 25.0, the ttable is 2.052, then tcount> ttable (9.315> 2.052). Then Ha is accepted and Ho is rejected. Thus it can be concluded that there are differences in social media addiction for the Pre Test and Post Test, so it can also be concluded that "there is an effect of information services through documentary film media on social media addiction in Angkasa Lanud Soewondo Junior High School students", while the amount of influence is 92.16%. Thus Information Services through documentary film media have an influence of 92.16% on social media addiction.